ANALYSIS OF THE MANAGEMENT AND PRESERVATION OF CULTURAL HERITAGE BUILDINGS BY THE LOCAL GOVERNMENT OF SALATIGA - Arina Diah Al Hamid; Laila Kholid Alfirdaus (Journal of Politic and Government Studies, 2018)
This study has the purpose of analyzing how the role of the Salatiga City Government and the extent to which efforts have been made by the government as a manifestation in the management and preservation of cultural heritage buildings. In it also discusses the factors that hinder and support efforts to manage and preserve cultural heritage buildings and what strategies are appropriate to overcome existing obstacles. This is interesting to study because the existence of a cultural heritage building in an area is a reflection of how the area navigated the changing times.This research is a qualitative research using a descriptive method, which is a method that describes the actual phenomena of what happened in the field and then analyzed it. Data collection techniques used in this research are observation, interviews, documentaries, and data analysis and interpretation. The theory used is preservation of cultural heritage through the application of public policy.The results of this study note that the Salatiga City Government is still not maximal in carrying out the management and preservation of cultural heritage buildings. This can be seen from the lack of policy to follow up on the Regional Regulations that have been made both through SK and Perwali. Thus the process of preserving cultural heritage buildings in the City of Salatiga is still not clear. It is known that one of the factors that hinder the preservation of the cultural heritage building itself is funding. On the positive side, there are still many people who care about the existence of cultural heritage buildings and the establishment of the Cultural Heritage Expert Team is a supporting factor in the management and preservation of cultural heritage buildings. In addition, the use of cultural heritage buildings in Salatiga also have various forms both for religious, social, educational and economic interests which are in accordance with the rules in Article 39 paragraph 1 of Regional Regulation No. 2 of 2015 concerning Management and Preservation of Regional Cultural Heritage. Keywords: cultural heritage building, management, preservation, policy, utilization, obstacles